STAKEHOLDERS’ PERCEPTIONS OF ACTIONAID’S SOCIAL AUDIT PROCESSES IN THE NORTHERN REGION OF GHANA - Yakubu, A.R; Donkor, S.A; Kudadze, S. (UDS International Journal of Development, 2016)
The concept of social audit or social accountability is monitoring and evaluation from the view point of beneficiary communities. The main objective of the study was to investigate stakeholders’ perceptions of the processes, benefits, challenges and prospects of social audit as practiced by Action Aid Ghana (AAG) in the northern region of Ghana. The Study employed the evaluative research design. Data was gathered from primary sources by administering semi-structured questionnaire and interview guide to a total of 109 respondents made up of Action Aid staff and partners as well as community members, selected using a multistage sampling procedure. The study found that, though AAG and partners had very elaborate accountability processes with potential benefits, their community partners were not able to practice social audit. This was because these processes were not effective in transferring the needed knowledge and skills to the communities. It is recommended that AAG and partners apply more participatory methodologies so that the community members are better equipped to hold their development partners accountable. KEYWORDS: ActionAid, Ghana, Northern region, Social audit